2017
DOI: 10.1163/22134808-00002591
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Changes in Sensitivity to Spatial and Temporal Properties of Sensory Integration Underlying Body Representation

Abstract: The closer in time and space that two or more stimuli are presented, the more likely it is that they will be integrated together. A recent study by Hillock-Dunn and Wallace (2012) reported that the size of the visuo-auditory temporal binding window — the interval within which visual and auditory inputs are highly likely to be integrated — narrows over childhood. However, few studies have investigated how sensitivity to temporal and spatial properties of multisensory integration underlying body representation d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…Sensitivity to temporal coincidence of rhythmic audiovisual stimuli, and to the congruency of native audiovisual speech stimuli, appear to emerge already within the first year of an infant’s life (Lewkowicz, 1996; Lewkowicz, 2003; Pons, Lewkowicz, Soto-Faraco, & Sebastián-Gallés, 2009). Yet, multisensory influences on perception and performance are nevertheless greatly reduced in young children when compared to adolescents and young adults (Brandwein et al, 2011; Burr & Gori, 2012; Ernst, 2008; Gori, Sandini, & Burr, 2012; Ross, Del Bene, Molholm, Frey, & Foxe, 2015; Ross et al, 2011) (Cowie, Makin, & Bremner, 2013; Cowie, Sterling, & Bremner, 2016) (Greenfield, Ropar, Themelis, Ratcliffe, & Newport, 2017). Several psychophysics studies found that children younger than eight years of age do not optimally integrate haptic and visual cues, but instead that prior to that point, one sense dominates the other, depending on the specific task demands (Gori, 2015; Gori, Del Viva, Sandini, & Burr, 2008; Gori et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Sensitivity to temporal coincidence of rhythmic audiovisual stimuli, and to the congruency of native audiovisual speech stimuli, appear to emerge already within the first year of an infant’s life (Lewkowicz, 1996; Lewkowicz, 2003; Pons, Lewkowicz, Soto-Faraco, & Sebastián-Gallés, 2009). Yet, multisensory influences on perception and performance are nevertheless greatly reduced in young children when compared to adolescents and young adults (Brandwein et al, 2011; Burr & Gori, 2012; Ernst, 2008; Gori, Sandini, & Burr, 2012; Ross, Del Bene, Molholm, Frey, & Foxe, 2015; Ross et al, 2011) (Cowie, Makin, & Bremner, 2013; Cowie, Sterling, & Bremner, 2016) (Greenfield, Ropar, Themelis, Ratcliffe, & Newport, 2017). Several psychophysics studies found that children younger than eight years of age do not optimally integrate haptic and visual cues, but instead that prior to that point, one sense dominates the other, depending on the specific task demands (Gori, 2015; Gori, Del Viva, Sandini, & Burr, 2008; Gori et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the distance between the real hand and the rubber hand has proven to modulate the strength of the illusion (Erro et al, 2020 ), with a significant decrease of illusory effect after a distance of 30 cm (Lloyd, 2007 ). Notably, developmental studies investigating multisensory processes suggest that the spatial distance and the temporal window within which multisensory stimuli are likely to be integrated into a unitary experience narrows over childhood (Greenfield et al, 2017 ), suggesting that children might partially perceive the RHI even during asynchronous conditions. Future investigation should investigate this possibility by systematically manipulating the length of temporal delay and spatial distance between visual and tactile stimulations in an RHI paradigm.…”
Section: Discussionmentioning
confidence: 99%
“…In Cowie et al's (2013) study, when visualtactile inputs were synchronous, both adults and children aged 4-9-years-old estimated the location of their unseen hand to be closer to the fake hand than in pre-touch baseline conditionsan indication that multisensory integration had taken place. However, unlike adults, even when visual-tactile inputs were asynchronous, 4-9 year old children's made estimates were also closer to the fake hand than in baseline conditions which might suggest either that visual capture by the fake hand dominates proprioception or that the temporal binding of visuo-tactile sensory information is not as tightly constrained in younger children as it is in older children and adults (Greenfield et al, 2015(Greenfield et al, , 2017. Therefore, the involvement of temporal processing in the RHI paradigm, makes it more difficult to determine the weighting of different sensory inputs.…”
Section: Introductionmentioning
confidence: 99%
“…In summary, although this body of research points to a maturation of sensory integration skills during childhood, the age at which children are reported to become adult-like in flexibly re-weighting sensory inputs appears to vary considerably. This could be due to the extent that the task relies on motor skills (i.e., pointing to the target/hand), temporal processing and/or working memory, all of which improve significantly over childhood ( Takahashi et al, 2003 ; Gathercole et al, 2004 ; Barkley et al, 2014 ; Greenfield et al, 2015 , 2017 ).…”
Section: Introductionmentioning
confidence: 99%